Penguatan Kompetensi Guru dalam Pengajaran Koding dan Kecerdasan Artifisial untuk Mendukung Pembelajaran Abad ke-21 di SMP Unggul Ahmad Dahlan - Effendi, Noverta; Afdal, Afdal; Vilmala, Berry Kurnia; Syaf putra, Rudi; farida, fitri (LPPM UMRI, 2026)
This community service program aims to strengthen teachers’ pedagogical and technological competencies in teaching coding and artificial intelligence as key 21st‑century learning skills at SMP Unggul Ahmad Dahlan. The program is motivated by teachers’ limited mastery of computational thinking and the design of AI‑based learning, which has constrained the optimal use of digital learning environments. Activities are carried out through a training and mentoring approach that includes hands‑on practice using block‑based and text‑based coding platforms, as well as the development of AI‑assisted instructional media aligned with the curriculum. The results indicate an increase in teachers’ understanding of basic coding concepts, their ability to design simple AI‑based projects, and their readiness to implement student‑centered learning scenarios supported by digital technologies. These outcomes suggest that systematically and contextually strengthening teacher capacity can help schools adapt to the demands of the Fourth Industrial Revolution and foster a stronger culture of digital literacy within the school environment.